1959
DOI: 10.1111/j.1476-5381.1959.tb01395.x
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of Amine Oxidase for Optically Active Substrates and Inhibitors

Abstract: A number of optically active amines have been tested as substrates or inhibitors of amine oxidase of rabbit and guinea-pig liver. The two stereoisomers of fl-hydroxyphenethylamine were oxidized at the same rate by rabbit liver, but the guinea-pig liver extracts oxidized the D form more rapidly than the L form. The two stereoisomers of amphetamine were equally active as inhibitors of the rabbit liver oxidase, but with guinea-pig liver extracts dexamphetamine, the (+) form, was more potent as an inhibitor. In bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

1959
1959
1978
1978

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Pratesi and Blaschko (1959), using rabbit liver as source of amine oxidase, found that the two stereoisomers of amphetamine were equally active as inhibitors. It is interesting that dexamphetamine, which in our experiments on rat liver proved to be as strong an inhibitor as (+ )-l-phenylethylamine, appears to be more active on amine oxidase from guinea-pig liver than on that from rabbit liver (Pratesi and Blaschko, 1959). Such findings emphasize the dependence of stereospecificity on animal species.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Pratesi and Blaschko (1959), using rabbit liver as source of amine oxidase, found that the two stereoisomers of amphetamine were equally active as inhibitors. It is interesting that dexamphetamine, which in our experiments on rat liver proved to be as strong an inhibitor as (+ )-l-phenylethylamine, appears to be more active on amine oxidase from guinea-pig liver than on that from rabbit liver (Pratesi and Blaschko, 1959). Such findings emphasize the dependence of stereospecificity on animal species.…”
Section: Discussionmentioning
confidence: 99%
“…Mann and Quastel (1940) suggested that central stimulation by amphetamine might be due to inhibition of amine oxidase. However, although in rabbit and man (+)-amphetamine (dexamphetamine) is a stronger stimulant than the (-) form, Pratesi and Blaschko (1959) have shown that the two stereoisomers are equally active as inhibitors of rabbit liver enzyme.To test the idea that amphetamine owes its analeptic properties to its inhibitory action on amine oxidase, it was clearly necessary to use amine oxidase from the same species as that used for the pharmacological experiments. It was also desirable to use amine oxidase from the brain in preference to liver, because the patterns of substrate and inhibitor specificities might vary in different organs.…”
mentioning
confidence: 99%
See 3 more Smart Citations